Advances in targeted therapies for metastatic colorectal cancer. Issue 3 (May 2009) - Perez-Garcia, Jose; Capdevila, Jaume; Macarulla, Teresa; Ramos, Francisco Javier; Elez, Elena; Ruiz-Echarri, Manuel; Tabernero, Josep
Colorectal cancer is one of the most frequently diagnosed malignancies in men and women and despite recent advances the prognosis of metastatic colorectal cancer remains poor. A better understanding of the molecular pathways that characterize tumor growth has provided novel targets in cancer therapy. Several proteins have been implicated as having a crucial role in metastatic colorectal cancer. Targets are defined according to their cellular localization, such as membrane receptor targets, intracellular signaling targets and protein kinases that regulate cell division. In the last 5 years, cetuximab, panitumumab and bevacizumab have been approved for the treatment of metastatic colorectal cancer and emerging data on the clinical development of new drugs, other than EGF-receptor and VEGF inhibitors, are likely to provide novel opportunities in the treatment of this malignancy.